Revitalizing Siri’ na Pacce Values through a Culture-Based Civic Education Model: Evidence from the PPKn Field School Prototype in Makassar - Muhajir Muhajir; Indah Ainun Mutiara; Akbar Aba (Journal of Moral and Civic Education, 2026)
solidarity (pacce) has become increasingly important for strengthening students’ civic competence amid globalization and the continued dominance of cognitively oriented civic education practices. This study aims to: (1) examine the contemporary meanings of Siri’ na Pacce in socio-cultural practices in Makassar; (2) develop a culture-based civic education model through the Civic Education Field School Budaya (FSB) prototype; and (3) assess its initial practicality and potential instructional effectiveness. This research employed a mixed methods Sequential Exploratory design. The qualitative phase involved in-depth interviews, field observations, document analysis, and limited implementation of the FSB prototype, while the quantitative phase consisted of an initial expert-based validation (N=2) to confirm perceptions of relevance, practicality, and perceived effectiveness. The findings reveal a meaningful gap between the philosophical values of Siri’ na Pacce and younger generations’ contemporary understanding, largely due to limited contextual and experiential learning opportunities. In response, the FSB model was developed through four instructional stages: orientation, field exploration, reflection-contextualization, and action-presentation, emphasizing participatory learning and authentic assessment. Initial findings indicate that the model demonstrates high contextual relevance and promising instructional potential, although further refinement is required, particularly regarding logistical arrangements, instructional time allocation, and affective assessment instruments. These findings contribute to the development of ethnopedagogical approaches in civic education by integrating local wisdom into transformative citizenship learning.